When Literary Censorship Is Not Strictly Enforced, Self-Censorship Rushes In - Ben-Ari, Nitsa (TTR)

(untitled) (Association canadienne de traductologie, 2010)
Understanding literary translation as part of a power game has led to renewed interest in issues of censorship in translation. In an effort to untangle the intricate relations between formal law and (internalized) norms, this essay will focus on voluntary or self-imposed censorship in areas where formal censorship (i.e., legislated law, religious law) is not strictly enforced. It will first briefly describe certain aspects of formal censorship in Israel, then present cases in which the borderline between formal censorship and self-censorship seems blurred. Two particular cases will be examined: one has to do with the attitude of translators towards the use of the words “pig and pork,” the other with the Committee established by the Ministry of Education in the 1960s to censor obscenity in literature. These cases will help shed light on the deep roots of self-censorship mechanisms and the reduced need for formal censorship when subordinate groups or individuals feel that working with the consensus is more beneficial than working against it. The case of a book banned in the Orthodox community—and therefore pre-censored for translation—will examine another aspect of censorship, that of the corrective measures applied when voluntary self-censorship is not exercised.